MELATONIN CAN NOT SIGNIFICANTLY INCREASE PLATELET COUNT - Tania Meysavira Fawzi; Lusiana Batubara; Asih Budiastuti; Taufik Eko Nugroho (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2021)
Background: Burn injury defines as skin or tissue damage caused by heat, radioactivity, electricity, or chemicals. Burn injury have an impact on physiological homeostasis. Burn injury will cause an increase in free radicals, it can also cause changes in the platelet count. Melatonin has been proposed as burn supportive therapy because it acts as an antioxidant that can eliminate free radicals. Melatonin can increase the number of the platelets through the mechanism of increasing megakaryocyte fragmentation and modulating the cytokines involved in platelet production. Aim: Proving the effects of melatonin supplementation on the number of platelets in male Wistar rats with third degree of burn injury. Methods: This research was an experimental with randomized control group pre-post test design. Samples are 12 healthy male Wistar rats then randomly divide into two groups, control and experimental group. Each rat was induced 30% burn injury under anesthesia. Rats in control group were given placebo at 0, 8, and 16 hours after burn injury, while rats in experimental group were treated with melatonin intraperitoneal at 0, 8 and 16 hours after burn injury. Blood samples were collected from the retroorbital sinuses at 0, 3, and 24 hours. Data were analyzed statistically by Paired t-Test and Independent t-Test. Results: In control group, the number of platelets at 0-3 hours (p=0,024) and 0-24 hours (p=0,039) showed a significant decrease in platelet count. In experimental group, the number of platelets at 0-3 hours (p=0,047), 0-24 hours (0,015), 3-24 hours (p=0,04) showed a significant decrease in platelet count.Conclusions: Melatonin administration did not cause a significant increase of platelets number. Keywords: Burns, Platelet count, Melatonin